ACCCN Workforce Standards for Intensive Care Nursing: Systematic and evidence review, development, and appraisal. Issue 5 (September 2018) - Chamberlain, Diane; Pollock, Wendy; Fulbrook, Paul; ,
Abstract: Background: The intensive care nursing workforce plays an essential role in the achievement of positive healthcare outcomes. A growing body of evidence indicates that inadequate nurse staffing and poor skill mix are associated with negative outcomes for patients, and potentially compromises nurses' ability to maintain the safety of those in their care. In Australia, the Australian College of Critical Care Nurses (ACCCN) has previously published a position statement on intensive care staffing. There was a need for a stronger more evidence based document to support the intensive nursing workforce. Objectives: To undertake a systematic and evidence review of the evidence related to intensive care nurse staffing and quality of care, and determine evidence-based professional standards for the intensive care nursing workforce in Australia. Methods: The National Health and Medical Research Council standard for clinical practice guidelines methodology was employed. The English language literature, for the years 2000-2015 was searched. Draft standards were developed and then peer- and consumer-reviewed. Results: A total of 553 articles was retrieved from the initial searches. Following evaluation, 231 articles met the inclusion criteria and were assessed for quality using established criteria. This evidence was used as the basis for the development of ten workforce standards, and to establish the overall level of evidence in support of each standard. All draft standards and their subsections were supported multi-professionally (median score >6) and by consumers (85–100% agreement). Following minor revisions, independent appraisal using the AGREE II tool indicated that the standards were developed with a high degree of rigour. Conclusion: The ACCCN intensive care nursing nurse workforce standards are the first to be developed using a robust, evidence-based process. The standards represent the optimal nurse workforce to achieve the best patient outcomes and to maintain a sustainable intensive care nursing workforce for Australia.